Analysis of the Migration of the Ucayali River and its Influence on the Territories of the Communities of the Jenaro Herrera District, Loreto, Peru - Caldas Carrillo, Corina Isabel (2025)
In the Supay-Sahua sector of the Jenaro Herrera District, the lateral migration of the Ucayali River has been eroding the banks of the Supay lagoon and during the 2022 flood it affected riparian forests and crops.  Therefore, this research analyzes the fluvial dynamics and annual migration of the meander curves of the Ucayali River with satellite images from the period 1985-2021 and proposes a future scenario through temporal regression analysis and with fluvial geomorphological analysis. potential fluvial processes. The results indicate that lateral migration of the Ucayali River is increasing in the meanders surrounding the Supay and Sahua lagoons. The Supay meander curve with a migration of 36.4 m/y could erode the shore of the Supay lagoon affecting 137 ha riparian forests and crops in the Once de Agosto and Nuevo Pumacahua communities in the medium term. Likewise, the Lobillo meander curve with a progressive migration of 86.5 m/a is heading towards Laguna Sahua, and in an estimated period of 21 years it could modify the alluvial plain with potential losses of 1013 ha of riparian forests, crops and resettlement for the Once de Agosto community. The changes in the landscape would affect local transportation.